Tecnomatix Plant Simulation: Modeling and Programming by Means of Examples - Bangsow, Steffen (Springer, 2015)
This book systematically introduces the development of simulation models as well as the implementation and evaluation of simulation experiments with Tecnomatix Plant Simulation. It deals with all users of Plant Simulation, who have more complex tasks to handle. It also looks for an easy entry into the program. Particular attention has been paid to introduce the simulation flow language SimTalk and its use in various areas of the simulation. The author demonstrates with over 200 examples how to combine the blocks for simulation models and how to deal with SimTalk for complex control and analysis tasks. The contents of this book ranges from a description of the basic functions of the material flow blocks to demanding topics such as the realization of a database-supported warehouse control by using the SQLite interface or the exchange of data by using XML, ActiveX, COM or DDE.